Property Issues Relating to Deep-Seabed Mining in the Light of the United Convention on the Sea of 1982 - Hennicke, Larisa (Europejskie Stowarzyszenie Studentów Prawa ELSA Poznań, 2014)
The study aims at the evaluation of the right to property in the context of the deep-seabed mining. The author present deep-seabed mining in the light of the United Convention on the Sea of 1982 focusing on the lack of knowledge about the oceans and the lack of regulations regarding the protection and enhancement of the oceans.
Keywords: right to property; deep-seabed mining; United Convention on the Sea of 1982